Assessment of vitamin D-related knowledge, attitudes and practices among Sultan Qaboos University students in Oman: a cross-sectional study - Rahma Said Al Hadhrami; Rehab Al Kaabi; Hajer Juma Al Shuaibi; Rawan Salim Al Abdulsalam (BMJ Public Health)
Background Vitamin D deficiency, a circulating level of 25-hydroxyvitamin D <30 nmol/L, has become an emerging public health issue in recent years. Despite being a sun-rich country, vitamin D deficiency is widespread in Oman (87.5%).Aim This study aimed to evaluate knowledge, attitudes and practices regarding vitamin D among university students in Oman to assess the need for additional awareness campaigns.Methods and sitting This descriptive, cross-sectional study was conducted from September to December 2022 and involved 399 students enrolled in various degree programmes at the Sultan Qaboos University (SQU) in Muscat, Oman, using self-administered, 38-item vitamin D-related KAP (D-KAP-38) questionnaire to collect information regarding the participants’ vitamin D-related general knowledge, nutritional knowledge, attitudes and practices.Results Of the 399 college students, 384 (96.2%) were Omani nationals, 283 (70.9%) were women and 255 (64.1%) were between the ages of 20 and 26 years. Overall, the participants demonstrated moderate general knowledge (mean D-KAP-38 score: 77.3), poor nutritional knowledge (mean D-KAP-38 score: 45.1), moderate attitudes (mean D-KAP-38 score: 64.4) and average practices (mean D-KAP-38 score: 60.0). In general, female students demonstrated greater general knowledge (p=0.004) and more positive attitudes (p=0.007) compared with males; however, males more frequently reported better practices (p<0.001). In addition, participants who lived off-campus reported better practices compared with those living on-campus (p<0.001).Conclusions University students in Oman demonstrated moderate vitamin D-related general knowledge, attitudes and practices, while nutritional knowledge was poor.